Viability mechanisms in market systems: prerequisites for market shaping. Issue 9 (21st May 2020) - Peters, Linda D.; Nenonen, Suvi; Polese, Francesco; Frow, Pennie; Payne, Adrian
Abstract : Purpose: This paper aims to develop a conceptual framework based on the identification and examination of the mechanisms (termed "viability mechanisms") under which market-shaping activities yield the emergence of a viable market: one able to adapt to the changing environment over time while remaining stable enough for actors to benefit from it. Design/methodology/approach: This paper uses extant literature to build a conceptual framework identifying viability mechanisms for market shaping and a case illustration examining how a viable market for Finnish timber high-rise buildings was created. The case exemplifies how the identified viability mechanisms are practically manifested through proactive market shaping. Findings: The proposed conceptual framework incorporates four viability mechanisms identified in the extant literature: presence of dissipative structures, consonance among system elements, resonance among system elements and reinforcing and balancing feedback loops. It illustrates how these mechanisms are manifested in a contemporary case setting resulting in a viable market. Practical implications: First, firms and other market-shaping organizations should look for, or themselves foster, viability mechanisms within their market-shaping strategies. Second, as failure rates in innovation are extremely high, managers should seek to identify or influence viability mechanisms to avoid premature commercialization of innovations. Originality/value: This study identifies how these viability mechanisms permit markets to emerge and survive over time. Further, it illuminates the workings of the non-linear relationship between actor-level market-shaping actions and system-level market changes. As such, it provides a "missing link" to the scholarly and managerial discourse on market-shaping strategies. Unlike much extant market-shaping literature, this study draws substantively on the systems literature.